Hypercapnia Impairs ENaC Cell Surface Stability by Promoting Phosphorylation, Polyubiquitination and Endocytosis of β-ENaC in a Human Alveolar Epithelial Cell Line - Gwoździńska, Paulina; Buchbinder, Benno A.; Mayer, Konstantin; Herold, Susanne; Morty, Rory E.; Seeger, Werner; Vadász, István (Frontiers in Immunology, 2017)
Acute lung injury is associated with formation of pulmonary edema leading to impaired gas exchange. Patients with acute respiratory distress syndrome (ARDS) require mechanical ventilation to improve oxygenation; however, the use of relatively low tidal volumes (to minimize further injury of the lung) often leads to further accumulation of carbon dioxide (hypercapnia). Hypercapnia has been shown to impair alveolar fluid clearance (AFC), thereby causing retention of pulmonary edema, and may lead to worse outcomes; however, the underlying molecular mechanisms remain incompletely understood. AFC is critically dependent on the epithelial sodium channel (ENaC), which drives the vectorial transport of Na+ across the alveolar epithelium. Thus, in the current study, we investigated the mechanisms by which hypercapnia effects ENaC cell surface stability in alveolar epithelial cells (AECs). Elevated CO2 levels led to polyubiquitination of β-ENaC and subsequent endocytosis of the α/β-ENaC complex in AECs, which were prevented by silencing the E3 ubiquitin ligase, Nedd4-2. Hypercapnia-induced ubiquitination and cell surface retrieval of ENaC were critically dependent on phosphorylation of the Thr615 residue of β-ENaC, which was mediated by the extracellular signal-regulated kinase (ERK)1/2. Furthermore, activation of ERK1/2 led to subsequent activation of AMP-activated protein kinase (AMPK) and c-Jun N-terminal kinase (JNK)1/2 that in turn phosphorylated Nedd4-2 at the Thr899 residue. Importantly, mutation of Thr899 to Ala markedly inhibited the CO2-induced polyubiquitination of β-ENaC and restored cell surface stability of the ENaC complex, highlighting the critical role of Nedd4-2 phosphorylation status in targeting ENaC. Collectively, our data suggest that elevated CO2 levels promote activation of the ERK/AMPK/JNK axis in a human AEC line, in which ERK1/2 phosphorylates β-ENaC whereas JNK mediates phosphorylation of Nedd4-2, thereby facilitating the channel–ligase interaction. The hypercapnia-induced ENaC dysfunction may contribute to impaired alveolar edema clearance and thus, interfering with these molecular mechanisms may improve alveolar fluid balance and lead to better outcomes in patients with ARDS.